2023
DOI: 10.1007/s11356-023-26566-5
|View full text |Cite
|
Sign up to set email alerts
|

Amsterdam urban water system as entry point of river plastic pollution

Abstract: Accumulation of plastic litter in aquatic environments negatively impacts ecosystems and human livelihood. Urban areas are assumed to be the main source of plastic pollution in these environments because of high anthropogenic activity. Yet, the drivers of plastic emissions, abundance, and retention within these systems and subsequent transport to river systems are poorly understood. In this study, we demonstrate that urban water systems function as major contributors to river plastic pollution, and explore the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Research on such travel dynamics in urban areas remains scarce. A recent study on Amsterdam found no significant correlations between rainfall and floating plastic transport in either of the six measured canals (Tasseron et al, 2023). For the Huveaune River in Marseille, Tramoy et al (2022) found that 36% of the annual macroplastic transport occurred during heavy rainfall events.…”
Section: Pluvial Floodsmentioning
confidence: 86%
See 1 more Smart Citation
“…Research on such travel dynamics in urban areas remains scarce. A recent study on Amsterdam found no significant correlations between rainfall and floating plastic transport in either of the six measured canals (Tasseron et al, 2023). For the Huveaune River in Marseille, Tramoy et al (2022) found that 36% of the annual macroplastic transport occurred during heavy rainfall events.…”
Section: Pluvial Floodsmentioning
confidence: 86%
“…Another complicating factor is that plastic pollution comes in countless different polymer types, shapes, rigidity, and sizes, which all influence the way they move through in the environment (van Emmerik & Schwarz, 2020). It is clear that plastic is a purely anthropogenic pollutant, and increased concentrations are generally observed close to densely populated areas (Kuizenga et al, 2023;Tasseron et al, 2023). However, large accumulations are found around the world in parallel.…”
Section: Introductionmentioning
confidence: 99%
“…It was also experimentally documented that microparticles formed via EPS and PS polymer fragmentation have smaller sizes than those released from PP and PET, with the largest formed from HDPE plastic (Boersma et al, 2023). Numerous riverine macroplastic waste items (e.g., cups, meat trays, plastic cutlery and straws, building insulation) are built from these fragmentation prone polymers (EPS, PS) (Plastic Europe 2021; Gonzalez-Fernandez et al, 2021;Tasseron et al, 2023). Gaining field-based information on their fragmentation rates seems to be especially important for our further understanding of the risks resulting from riverine macroplastic pollution.…”
Section: Polymer Typementioning
confidence: 99%
“…Regardless of the type of waste and its destination in the environment, urban areas are the main source of litter pollution in water bodies. For instance, recent estimates for the city of Amsterdam suggest that around 2.7 million items enter the closely connected IJ river annually (Tasseron et al, 2023).…”
Section: Introductionmentioning
confidence: 99%